Practical experiences with eribulin in patients with metastatic breast cancer - Tesch, Hans; Schneeweiss, Andreas (Anti-cancer drugs, 2016)
There is currently no standard therapy for women with metastatic or locally recurrent breast cancer. The microtubule polymerization inhibitor eribulin, approved in March 2011, is the first monochemotherapy with a proven survival benefit and tolerable toxicity in this patient group. Using a retrospec